The Influence of Employee Professionalism and Service Quality on Player (Golfer) Satisfaction at Imperial Golf Club Lippo Village Karawaci - Sinaga, Noptika Lesrini Br; Hia, Era Era; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
Amidst the intense competition in the golf industry in Tangerang, this study highlights the importance of service quality and employee professionalism in creating customer satisfaction and loyalty as a source of company profits.The Concept of Professionalism (Martin Jr. in Kurniawan, 2020) Reliability in carrying out tasks with good quality and simple procedures. Measured through four dimensions: Equality, Equity, Loyalty, and Accountability. Service Quality Concept (Parasuraman & Berry in Ratminto & Atik, 2018) - A dynamic condition that meets or exceeds customer expectations. Measured through 5 dimensions: Tangible (physical evidence), Reliability, Responsiveness, Assurance, and Empathy. Customer Satisfaction (Kotler & Keller, 2016) - The comparison of product/service performance with expectations. Measured through 5 indicators: Loyalty, Repurchase, Recommendation, Willingness to pay more, and Feedback.This research uses a descriptive quantitative case study method which is carried out by comparing the opinions of respondents who were recorded by distributing questionnaires to 93 respondents consisting of golf players. The analysis method uses SPSS version 25 for windows.The results of the study found: (1) A 49.4% partial or individual influence of Employee Professionalism to Player Satisfaction at Imperial Golf Club Lippo Karawaci. 47.5% influence of Service Quality to Player (Golfer) Satisfaction at Imperial Golf Club Lippo Village Karawaci. 61.7% influence of Employee Professionalism and Service Quality simultaneously or together to Player (Golfer) Satisfaction at Imperial Golf Club Lippo Village Karawaci.